THE INFLUENCE OF TEAMWORK, COMPENSATION AND WORK ETHIC ON THE WORK EFFECTIVENESS OF CIVIL SERVANTS OF THE ENVIRONMENTAL DEPARTMENT OF BANTUL DISTRICT - Widyaningsih , Asty; Kirana, Kusuma Chandra; Kusuma , Nala Tri (International Conference on Humanity Education and Society (ICHES), 2024)
Work effectiveness is an activity that humans usually carry out both physically and spiritually to achieve a result in accordance with the work that has been determined. Several factors that can increase work effectiveness include teamwork, compensation and work ethic. This research aims to examine the influence of teamwork, compensation and work ethics on the work effectiveness of civil servants at the Bantul district social service. This research is quantitative using saturated sampling, namely the population of the Bantul Regency Environmental Service. Data collected through distributing questionnaires directly to respondents. The results of this research show that Teamwork, Compensation and Work Ethics have a significant positive effect on Work Effectiveness. Teamwork, compensation and work ethics have significant implications for work effectiveness in an agency or organization